Financial autonomy of the universities in focus: case study of the State University of Piauí, Brazil (Research, Society and Development, 2020)
The CF / 1988 enshrined the university autonomy, article 207, unfolding it in three indissoluble facets: (i) didactic-scientific; (ii) administrative; and (iii) financial and asset management. This article focuses on the latter, providing an overview of the process of financial autonomy of Brazilian universities, maintained by state governments. The research was based on the reality of the State University of Piauí-UESPI, as well as the collection and expenditures made by the State Government for its maintenance in a 10-year cut (2008-2017). There is a comparison between the autonomy models performed in São Paulo and Paraíba. In the end, we propose financial autonomy based on the reality of Piauí and the relationship between the budget approved by LOA and the budget executed by UESPI, demonstrating the feasibility of incorporating financial autonomy into UESPI without negatively impacting state finances, at the same time. adequate resources are guaranteed to enable the university to play its role with quality.